The Role of Identities in Jordan AIgebras (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
Born of quantum mechanics, but abandoned at birth by physicists, Jordan algebras recovered to lead a productive life in a variety of mathematical fields.